Epistemologi Qawa'id Tafsir Dalam Dialektika Antara Otoritas Teks Dan Fluiditas Makna - Muhammad Fikran Said; Mardan Mardan; Rosmini Amin (Jurnal Ilmu Agama Indonesia, 2026)
This study discusses the epistemology of qawa’id tafsir in the dialectic between textual authority and the fluidity of meaning in Qur’anic interpretation studies. The study is motivated by the emergence of various interpretative approaches that seek to preserve the sacredness of the Qur’anic text while responding to the social dynamics of modern society. This research employs a qualitative approach using library research methods. Data were obtained from classical tafsir books, tafsir methodology references, scientific journals, and various literature related to contemporary tafsir epistemology. Data collection techniques were carried out through documentation studies and literature analysis, while data analysis used descriptive-analytical methods with a hermeneutic approach. The results indicate that the epistemology of qawa’id tafsir has evolved from a textual approach toward contextual and multidisciplinary approaches. Qawa’id tafsir functions as a methodological instrument to maintain balance between the authority of the Qur’anic text and interpretative dynamics influenced by social, cultural, and scientific developments. The dialectic between textual authority and the fluidity of meaning has produced diverse forms of interpretation that enrich Islamic intellectual traditions, although it also raises challenges regarding the legitimacy of interpretation. This study concludes that the development of adaptive, moderate, and contextual qawa’id tafsir is essential to ensure that Qur’anic interpretation remains relevant to contemporary societal issues without losing the fundamental values of Islamic teachings.